EDITORIAL : EMPOWERING INDUSTRY AND TRANSFORMING SOCIETY TOWARDS SUSTAINABLE DEVELOPMENT - Yee Yong, Lee; Sim Nee, Ting (Penerbit UMT, 2022)
This special issue presents the selected peer-reviewed full-text papers from the 13th International UNIMAS Engineering Conference 2020 (EnCon 2020), which was successfully organised through an online platform on October 27-28, 2020 by the Faculty of Engineering of Universiti Malaysia Sarawak (UNIMAS), Malaysia, along with various prominent co-organizers, the Institution of Engineers, Malaysia (IEM), Swinburne University of Technology, Malaysia, SRM Institute of Science and Technology, India, the Institute of Electrical and Electronics Engineers (IEEE), Malaysia and Universiti Teknologi PETRONAS (UTP), Malaysia.